Emergency Department Patient Experience of Care Survey Development and Field Test - Weinick, Robin M. (RAND Corporation, 2014)
The Centers for Medicare & Medicaid Services have implemented Consumer Assessment of Healthcare Providers and Systems (CAHPS®) surveys to assess patient experience in a number of settings. Following CAHPS principles, RAND researchers designed and field tested an Emergency Department Patient Experience of Care Survey that consists of three survey instruments for use with adult patients who have visited the emergency department.